Mosque-Based Economic Development Over a Decade with Bibliometric Review Analysis - Rusdi, Wahyudi; Wahyu Firmansyah; Hajrahwati Tahir (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2023)
This research aims to create a research map from studies conducted on mosque-based economic development. Using bibliometric analysis using Vosviewer. A total of 933 articles from 2013-2022 indexed by Scopus were used in this research. The results show a significant increase in the number of published research articles from 2013 to 2016. However, in the following years, from 2017 to 2022, there was a decrease in the number of research articles published. A very popular article is "Assessing the Economic Impact of Cultural Heritage Sites Using a Social Accounting Matrix: The Case of the Mosque-Cathedral of Cordoba," written by Campoy-Munoz, Pilar, Cardenete, M. Alejandro, and Delgado, M. Carmen. in 2017 with 32 citations and citations per year 5.33. Among researchers, Malik S has written and published the highest number of journals related to mosque empowerment, with a total of 7 research articles. Some topics that are often discussed are community-based, zakat, and infaq. Topics that are still rarely discussed include waqaf, agencies, management, COVID-19, and Islamic boarding schools.